When combined X‐ray and polarized neutron diffraction data challenge high‐level calculations: spin‐resolved electron density of an organic radical. Issue 4 (1st August 2017) - Voufack, Ariste Bolivard; Claiser, Nicolas; Lecomte, Claude; Pillet, Sébastien; Pontillon, Yves; Gillon, Béatrice; Yan, Zeyin; Gillet, Jean-Michel; Marazzi, Marco; Genoni, Alessandro; Souhassou, Mohamed
Abstract : Experimental joint refinement against X‐ray and polarized neutron diffraction data has been performed to simultaneously model the charge and spin density of a free radical; the resulting model challenges density functional theory (DFT) calculations, but is in fair agreement with ab initio complete active‐space self‐consistent field (CASSCF) calculations. Abstract : Joint refinement of X‐ray and polarized neutron diffraction data has been carried out in order to determine charge and spin density distributions simultaneously in the nitronyl nitroxide (NN) free radical Nit(SMe)Ph. For comparison purposes, density functional theory (DFT) and complete active‐space self‐consistent field (CASSCF) theoretical calculations were also performed. Experimentally derived charge and spin densities show significant differences between the two NO groups of the NN function that are not observed from DFT theoretical calculations. On the contrary, CASSCF calculations exhibit the same fine details as observed in spin‐resolved joint refinement and a clear asymmetry between the two NO groups.